2015
DOI: 10.3111/13696998.2015.1067623
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and healthcare costs of obesity-related comorbidities: evidence from an electronic medical records system in the United States

Abstract: ORCs are associated with substantial economic burden, especially for those requiring continuous treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 14 publications
2
50
0
Order By: Relevance
“…Li et al provided the prevalence and healthcare costs of obesity‐related comorbidities (OCR). They identified 10 comorbidities, prevalent above a 10% threshold, which were more prevalent in the population of people with obesity than for the population of people without obesity and identified that hypertensive diseases, dyslipidaemia and osteoarthritis were the most expensive ORCs for this population . Given how costly hypertensive disease and dyslipidaemia are as co‐morbidities it is imperative to understand the prevalence of multimorbidity patterns that include them.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Li et al provided the prevalence and healthcare costs of obesity‐related comorbidities (OCR). They identified 10 comorbidities, prevalent above a 10% threshold, which were more prevalent in the population of people with obesity than for the population of people without obesity and identified that hypertensive diseases, dyslipidaemia and osteoarthritis were the most expensive ORCs for this population . Given how costly hypertensive disease and dyslipidaemia are as co‐morbidities it is imperative to understand the prevalence of multimorbidity patterns that include them.…”
Section: Discussionsupporting
confidence: 65%
“…Alternatively providing unnecessary services leads to resource wastage. 33 Our results provide prevalent patterns of three or more chronic conditions including obesity. 32 Patients need these issues addressed as soon as possible during care, which requires early screening and targeted management.…”
Section: Patient Segmentation With Fp-growthmentioning
confidence: 72%
See 1 more Smart Citation
“…23 A similar pattern has been observed in developed nations. 24,25 Our findings also point out that primary care services have strategic relevance regarding preventive actions aimed towards controlling obesity and its future complications.…”
Section: Discussionmentioning
confidence: 85%
“…The obesity incidence in the United States has been increasing since the late 20th century, with 30% to 40% of adults currently classified as overweight and 35% classified as obese [13]. Increasing body mass is associated with comorbid conditions that adversely affect life expectancy and overall medical expenditures [4, 5].…”
mentioning
confidence: 99%